Memahami Kompetensi Tenaga Kependidikan Di MIN 1 KUTAI TIMUR - Ratih fatonah; Irma; Muhammad Zidan. M; Muhammad Syahrul. R (PT. Pustaka Andil Lestari, 2024)
This study explores the competency of education staff at MIN 1 Kutai Timur, a state Islamic Islamic school in East Kutai Regency, East Kalimantan, Indonesia. The competence of educational staff is perceived as a key factor in achieving optimal quality of education in the madrasah. Through a qualitative approach using interview methods, this study collected in-depth data about the profile, qualifications, perceptions, evaluations, training, challenges and leadership support for the competence of educational staff. Findings show that leadership actively supports activities and training aimed at increasing competence, especially those related to the use of digital technology such as the Si Pintar application. Efforts to increase the competency of education staff at MIN 1 Kutai Timur have shown positive results in terms of performance and quality of education. Even though the performance assessment shows good results, improvements continue to be made to ensure that the quality of education gets better in the future. Overall, the commitment and hard work of all education staff as well as support from school leaders creates an environment that supports increasing competency and quality of education at MIN 1 Kutai Timur. Despite facing challenges such as limited quality human resources and technological infrastructure, strong support from school leaders has had a positive impact on improving the quality of education at MIN 1 Kutai Timur.